2014
DOI: 10.1002/2327-6924.12043
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the concept of collaboration within the context of nurse practitioner-physician collaborative practice

Abstract: Purpose Collaboration in the healthcare setting is a multifaceted process that calls for deliberate knowledge sharing and mutual accountability for patient care. The purpose of this analysis is to offer an increased understanding of the concept of collaboration within the context of nurse practitioner (NP)‐physician (MD) collaborative practice. Data sources The evolutionary method of concept analysis was utilized to explore the concept of collaboration. The process of literature retrieval and data collection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…"Teamwork," however, is defined as a group of people working interdependently to achieve a common goal 9 and "collaboration" is defined as 2 clinicians consulting with each other and working concurrently by sharing knowledge and expertise to achieve optimal patient care. 15 Evidence is clear about the benefits of team-based and collaborative care, 16 yet researchers have concluded that evidence is lacking about comanagement approaches to care. 17 Team-based care and collaborative care with nurse practitioners often involve a hierarchy with team members aligned in a vertical organizational structure based on profession or role.…”
Section: Similar Termsmentioning
confidence: 99%
“…"Teamwork," however, is defined as a group of people working interdependently to achieve a common goal 9 and "collaboration" is defined as 2 clinicians consulting with each other and working concurrently by sharing knowledge and expertise to achieve optimal patient care. 15 Evidence is clear about the benefits of team-based and collaborative care, 16 yet researchers have concluded that evidence is lacking about comanagement approaches to care. 17 Team-based care and collaborative care with nurse practitioners often involve a hierarchy with team members aligned in a vertical organizational structure based on profession or role.…”
Section: Similar Termsmentioning
confidence: 99%
“…The NP and physician share knowledge, clinical expertise, decision making, and problem solving. In addition, the NP and physician can consult each other and share their plan of care to achieve good patient care outcomes (Bailey, Jones, & Way, ; Bridges, ). Most states, including Alabama, Georgia, Connecticut, New York, and Pennsylvania, require physician collaboration in NP practice (Buppert, ; Guido, ).…”
Section: Supervision Collaboration and Protocolmentioning
confidence: 99%
“…Collaborative practice is complex and multifaceted (Bridges 2014). Interventions to improve collaborative practice and provide clear information about roles can facilitate collaboration and ultimately improve patient care (Schadewaldt 2013).…”
Section: Introductionmentioning
confidence: 99%